Study of antioxidant and free radical scavenging activities of methanolic extract of Rumex acetosella roots and its fractions in different solvents - Dildar Ahmed,; Qaria Mumtaz Anwar Mughal, (International Journal of Phytomedicine, 2013)
The context and purpose of the study: In view of the wide ethnomedicinal applications of Rumex acetosella, and as part of our quest for natural antioxidants, the present research was designed to evaluate antioxidant and free radical scavenging activities of the methanolic extract of its roots and its sub-fractions in solvents of different polarity employing DPPH free radical scavenging, ABTS, FRAP, phosphomolybdate, reducing power and lipid peroxidation assays. Main findings: The MeOH extract and its fractions exhibited considerable antioxidant potential. The n-butanol fraction, having highest phenolic and flavonoid contents, 252.19 μg/mL of gallic acid equivalent and 891.34 μg/mL of rutin equivalent respectively, was most potent. All the fractions efficiently scavenged the DPPH free radical; n-butanol fraction was most powerful and had the lowest EC50 (212.36 μg/ mL) and TEC50 (4 min). The phosphomolybdate antioxidant activity of the plant extracts ranged from 325.41-82.47 μg/mL of AAE (Ascorbic Acid Equivalent). The n-butanol fraction had the highest FRAP, or ferric reducing antioxidant potential, value (569.52 μg/mL of AAE) and the highest Trolox equivalent antioxidant capacity, or TEAC, value (1747.71 mM) in ABTS assay. The chloroform fraction that was least active in all the assays showed the lowest TEAC value (638.87 mM). Brief summary and potential implications: The polar fractions of the MeOH extract of the roots of R. acetosella, having higher phenolics and flavonoids, displayed noteworthy antioxidant properties, the n-butanol fraction being the most powerful. Results present the plant as a potential source of natural antioxidants.